2019
DOI: 10.1111/jfpp.14234
|View full text |Cite
|
Sign up to set email alerts
|

Improving the characteristics of spreadable processed cheese using Konjac and Xanthan gums

Abstract: The effects of konjac (0%–0.4% w/w) and xanthan (0%–0.4% w/w) gums on pH, sensory (taste, spreadability, firmness), and textural characteristics (hardness, adhesiveness, cohesiveness, springiness, gumminess, chewiness) of spreadable processed cheese were investigated. The central composite design (CCD) was used and the data were analyzed using response surface methodology (RSM). The results showed that adding konjac and xanthan reduced the pH of the cheese. Regarding the sensory characteristics, the results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
(30 reference statements)
0
3
1
Order By: Relevance
“…Also, Salvatore et al ( 2014 ) found that fresh cheese samples containing inulin had lower adhesiveness (Salvatore et al, 2014 ). The opposite of our findings, Ghods Rohani and Rashidi ( 2019 ) reported that adding konjac and xanthan to spreadable processed cheese increased adhesiveness (Ghods Rohani & Rashidi, 2019 ). Zheng et al ( 2016 ) pointed out that the adhesiveness of sliced cheese was correlated positively with fat content (Zheng et al, 2016 ).…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…Also, Salvatore et al ( 2014 ) found that fresh cheese samples containing inulin had lower adhesiveness (Salvatore et al, 2014 ). The opposite of our findings, Ghods Rohani and Rashidi ( 2019 ) reported that adding konjac and xanthan to spreadable processed cheese increased adhesiveness (Ghods Rohani & Rashidi, 2019 ). Zheng et al ( 2016 ) pointed out that the adhesiveness of sliced cheese was correlated positively with fat content (Zheng et al, 2016 ).…”
Section: Resultscontrasting
confidence: 99%
“…Contrary to our results, Hosseini‐Parvar et al ( 2015 ) found that an increment in the level of basil seed gum resulted in more hardness in processed cheese (Hosseini‐Parvar et al, 2015 ). Also, adding tragacanth gum into Lighvan cheese, konjac, and xanthan gums into spreadable processed cheese increased hardness and firmness (Ghods Rohani & Rashidi, 2019 ; Milani et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations